The Influence of Location And E-Wom on Purchasing Decisions Through Purchase Interest: Study of Kebon Kopi Cakkin Coffee Shop Consumers in Malang City - Muhamad Bintang Iqbal Mauludin; Fani Firmansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study investigates the direct and indirect effects of geography and electronic word-of-mouth (E-WOM) on purchasing decisions, with purchase interest serving as a mediator. Employing a quantitative survey methodology, primary data was collected through questionnaires from 136 consumers of Coffee Shop Kebon Kopi Cakkin in Malang City, and analyzed using Smart PLS 4.0 statistical software. The results indicate that location has a positive and significant impact on purchase interest, but a negative and insignificant effect on purchasing decisions. Conversely, E-WOM is shown to positively and significantly influence both purchase interest and purchasing decisions, while purchase interest itself also has a significant positive effect on purchasing decisions. Furthermore, it was found that location positively influences purchasing decisions through purchase interest, and E-WOM similarly impacts purchasing decisions via purchase interest among consumers at Coffee Shop Kebon Kopi Cakkin. The implications of these findings are substantial for marketers and business owners. Recognizing that geographic factors can enhance consumer interest emphasizes the importance of location for attracting customers. This insight can guide businesses in selecting optimal sites for new branches and shaping their marketing strategies to exploit geographic advantages. Furthermore, the significant positive influence of E-WOM on both purchase interest and decisions highlights the necessity for businesses to actively cultivate favorable online reviews and customer testimonials. Engaging with consumers on digital platforms can build trust and improve overall reputation. By concentrating on these key elements, coffee shops and similar businesses can strengthen their positions in the competitive market, leading to increased sales and enhanced customer loyalty. Overall, this study underscores the value of integrating geographic considerations and social influence in developing targeted marketing strategies that effectively resonate with consumer behavior and purchasing patterns.